Mapping Subtitling in KSA in Relation to Saudi Vision 2030: A Sociological and Historical Analysis - Altalidi, Bandar; Alqarni, Abdullah; Sahari, Yousef (Jurnal Arbitrer, 2025)
The production and consumption of subtitled content in the Kingdom of Saudi Arabia (KSA) have undergone various developments, experiencing periods of both progress and decline. However, this topic is largely ignored and insufficiently researched. Consequently, this paper addresses this lack of detailed socio-historical research into the cultural production of subtitling in KSA. It therefore traces the trajectories of subtitling as a social practice, examining the external and internal factors that (re) shape its dynamics since the 1950s. Inspired by technological and socio-cultural developments, subtitling is analysed in this paper as a social field, inhabited by various agents who deploy different strategies to accumulate capital. Adopting a qualitative approach and building on the sociology of Pierre Bourdieu, this paper analysed the subtitling field according to three historical periods. Following this thematic and periodisation analysis, each period documents the external factors influencing the development of the field and identifies the main agents along with their motivations and position-takings. To ensure the reliability and validity of research, triangulation of data sources and methods is adopted. Data are collected from archival sources, observation, published reports, audiovisual content and previous studies. The application of this sociological analysis provides an in-depth understanding of the evolving nature of the subtitling field concerning the concept of power. More importantly, the study of this social field assesses the influence of Saudi Vision 2030 (SV2030) on the cultural production in KSA, including subtitling. This paper concludes that the socio-cultural developments promoted by SV2030 have been crucial in restructuring the field’s dynamics, leading to significant changes in audiovisual production and consumption. The analysis suggests that 2016 marked a distinctive era for subtitling in KSA, compared to previous periods and developments. The paper contributes to the ongoing discussion on sociological approaches in translation studies by focusing on the application of Bourdieu’s theory to audiovisual translation. It extends the application of this theory to the digital forms of translation, emphasising the usefulness of Bourdieu’s sociology to digital fields.